2014
DOI: 10.1590/s1415-43662014000700004
|View full text |Cite
|
Sign up to set email alerts
|

Metais pesados em girassol adubado com lodo de esgoto submetido a diferentes processos de estabilização

Abstract: O lodo de esgoto apresenta grande potencial para utilização agrícola; entretanto, esta forma de disposição final causa preocupação uma vez que existe a possibilidade de inserção de metais pesados na cadeia alimentar. Objetivou-se, com este trabalho, avaliar os teores de metais pesados no solo e na planta de girassol em resposta à adubação com lodo de esgoto submetido a diferentes processos de estabilização. O experimento foi desenvolvido em Cambissolo Háplico com os tratamentos: testemunha (sem adubação), adub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
(21 reference statements)
1
9
0
4
Order By: Relevance
“…375 of 2006 provides that the maximum total content of As, Cu and Zn in sanitary sewage sludge is 41; 1,500 and 2,800 mg kg -1 , respectively (Brasil, 2006), these limits much higher than those found in sanitary sewage sludge used in this study (Table 2). Nascimento et al (2014) also found lower total contents of Cd, Cr, Cu, Ni, Pb and Zn in relation to the legislation for sanitary sewage sludge, under different stabilization processes, to be used in agricultural cultivation areas.…”
Section: Total Content Of As Cu and Zn In Sanitary Sewage Sludge Andmentioning
confidence: 83%
“…375 of 2006 provides that the maximum total content of As, Cu and Zn in sanitary sewage sludge is 41; 1,500 and 2,800 mg kg -1 , respectively (Brasil, 2006), these limits much higher than those found in sanitary sewage sludge used in this study (Table 2). Nascimento et al (2014) also found lower total contents of Cd, Cr, Cu, Ni, Pb and Zn in relation to the legislation for sanitary sewage sludge, under different stabilization processes, to be used in agricultural cultivation areas.…”
Section: Total Content Of As Cu and Zn In Sanitary Sewage Sludge Andmentioning
confidence: 83%
“…The contents of the elements Fe, Zn, Cu, Mn, Al and Se decreased with the DE addition to the vermicomposting process (Table 2), since this residue has low contents of these elements in its composition (Table 1) Nascimento et al (2014) in vermicompost of SS and plant residues, which were equal to 374 and 71 mg kg -1 , respectively. For Fe and Mn, Hashemimajd & Jamaati-e-Somarin (2011) reported contents ranging from 3,000 to 6,000 mg kg -1 and from 225 to 300 mg kg -1 , respectively, in vermicompost of SS and plant residues.…”
Section: Resultsmentioning
confidence: 99%
“…There was a trend towards bioindicator higher dry matter yield from the increase of the biosolid dose. This may be justified by the fact that biosolids appear as a source of plant essential nutrients (Nascimento et al, 2014). Depth increase in the test column also provided higher dry matter yield ( Figure 1D).…”
Section: Picloram + 24-d Leaching Testmentioning
confidence: 95%